2021
DOI: 10.3390/ijms22147558
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Grafted 3D Superlattice Self-Assembly

Abstract: The exploitation of new methods to control material structure has historically been dominating the material science. The bottom-up self-assembly strategy by taking atom/molecule/ensembles in nanoscale as building blocks and crystallization as a driving force bring hope for material fabrication. DNA-grafted nanoparticle has emerged as a “programmable atom equivalent” and was employed for the assembly of hierarchically ordered three-dimensional superlattice with novel properties and studying the unknown assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
(138 reference statements)
0
10
0
Order By: Relevance
“…This limitation stems from the fact that there are possibilities of unwanted hybridization between partially complementary strands that belong to the same particle, as well as the possibilities of formation of secondary structures such as hairpin, which eventually results in loss of binding sites [ 62 , 63 ]. It is also challenging to synthesize a colloid grafted with different sequences which contributes to relatively sparse studies involving such building blocks [ 9 , 64 ].…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…This limitation stems from the fact that there are possibilities of unwanted hybridization between partially complementary strands that belong to the same particle, as well as the possibilities of formation of secondary structures such as hairpin, which eventually results in loss of binding sites [ 62 , 63 ]. It is also challenging to synthesize a colloid grafted with different sequences which contributes to relatively sparse studies involving such building blocks [ 9 , 64 ].…”
Section: Challengesmentioning
confidence: 99%
“…An alternate way of creating anisotropic interactions while using spherical colloids is to create DNA-functionalized Janus particles [ 9 , 64 , 65 , 66 , 67 , 68 , 69 ]. It has been found that these Janus particles self assemble into structures that are more complex and diverse than the closed packed crystals.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, DNA-linked 3D superlattices composed of metallic NPs have been investigated. 33,35,37,39,[42][43][44][45] In their pioneering work, Mirkin and Schatz have shown that such 3D supercrystals exhibit strong novel optical behaviours resulting from the coexistence of plasmonic and photonic modes. 28,35,46,47 By continuously varying the NPs orientation, periodicity, spacing, size, and shape, as well as the crystal habit, an enormous set of fundamentally interesting metamaterials can be designed.…”
Section: A Introductionmentioning
confidence: 99%
“…[22][23][24] A route to overcoming these limitations and achieving sustainable materials with improved optical properties consists of structuring the plasmonic building blocks in a well-organized manner, 25 forming one-dimensional (1D) chains, [26][27][28] two-dimensional (2D) arrays, [28][29][30][31][32] or threedimensional (3D) superlattices. 8,28,[33][34][35][36][37][38][39][40][41][42] These supercrystals possess the unique ability to retain the intrinsic properties of their building blocks but also display unique collective properties originating from interparticle coupling effects. In recent years, DNA-linked 3D superlattices composed of metallic NPs have been investigated.…”
Section: Introductionmentioning
confidence: 99%